Evolution of Indian monsoon precipitation and vegetation dynamics in the Bay of Bengal region since the last glacial period - Rahman, Ananna; Luo, Chuanxiu; Khan, Md Hafijur Rahaman; Wan, Sui; Yang, Yiping; Wei, Haicheng; Xiang, Rong; Zhang, Lanlan; Liu, Jianguo; Su, Xiang; Huang, Yun (Quaternary science reviews, 2025)
The Indian Summer Monsoon (ISM) is among the major global climate systems and influences one-quarter of the world's population. However, the long-term variability of ISM precipitation from the last glacial to the present remains a subject of major debate. One debate concerns the precipitation change driven by the ISM from Marine Isotope Stage (MIS) 2 to MIS 1, while another focuses on the varying degrees of monsoonal rainfall intensity across different warm periods (MIS 3 and MIS 1). In this study, we reconstruct high-resolution palynological records from two sediment cores (YDY10 and E87-32B) in the Bay of Bengal (BoB) to explore changes in regional vegetation and ISM precipitation since the last glacial period. The results show that the concentrations of terrigenous pollen-spore decrease with increasing offshore distance, primarily reflecting pollen-spore input and transportation from the Ganges-Brahmaputra (G-B) river basins. Significant shifts in evergreen broad-leaved pollen at ∼40.5 ka and ∼12 ka indicate notable changes in hydrodynamic forces and intense precipitation, reflecting strong ISM activity. Data from core E87-32B indicate that ISM precipitation during the early to middle Holocene (MIS 1) was higher than during MIS 3, likely influenced by summer solar insolation (SSI) on an orbital timescale. From the Last Glacial Maximum (LGM) to the middle Holocene in MIS 1, the region experienced a transformation from extensive herbaceous vegetation to tropical and subtropical broad-leaved forests, followed by millennial-scale fluctuations in ISM precipitation in both cores. In core YDY10, broad-leaved forest pollen shows three distinct low values corresponding to Heinrich 1 (H1), Younger Dryas (YD), and the 8.2 ka cold and dry events, respectively, consistent with variations in the weakened Atlantic meridional overturning circulation (AMOC). Meanwhile, in core E87-32B, the broad-leaved pollen percentage increase from the LGM to the early and middle Holocene, indicating stronger ISM precipitation and G-B river input. This suggests that the ISM variation in this period was driven by AMOC and other factors, such as river input. Overall, this study offers a comprehensive perspective on past climate and vegetation dynamics around the BoB region on orbital and millennial timescales and contributes to a better understanding of the controls on monsoonal rainfall under different boundary conditions. •PCA highlights that broadleaved tree pollen values in both cores are influenced by precipitation.•Greater ISM precipitation in MIS 1 than in MIS 3 was influenced by summer solar insolation.•Three low values of broad-leaved pollen of YDY10 correspond to H1, YD, and 8.2 ka events respectively.•In core E87-32B, the pollen value of broad-leaved forests increases from the LGM to the Holocene.•ISM variations from LGM to the Holocene linked to AMOC, and river inputs.